The Implementation of Inheritance Rights Distribution for Children Born Outside of Marriage According to Islamic Law in the Application of the Inheritance Law System in Indonesia - Inayatillah Ridwan; Neni Ruhani; Neneng Nurhasanah; Lina Jamilah (Leges Privatae, 2025)
This study discusses how the implementation of the inheritance rights of children born outside of marriage according to Islamic law in the application of the inheritance law system in Indonesia. In Islamic law, children born from a legitimate relationship have clear rights to their parents' inheritance. However, for children born outside of marriage, the situation becomes more complex. In many communities, social stigma and negative views of children born outside of marriage often affect their acceptance of inheritance rights. This can lead to injustice and discrimination, where these children do not get the rights they should receive according to Islamic law. The research method with a qualitative research type, this study uses library research, namely research that focuses and limits its activities to libraries to obtain data without conducting research in the field. Data collection techniques by conducting review studies of books, literature, notes, and reports that are related to the problem to be solved. Data sources in this study were obtained by tracing literature and laws and regulations, books, the Qur'an, and hadiths related to the research. Data collection techniques are carried out using documentary techniques. Documentary comes from the word document which means written object. In using the documentary method, the author collects written data such as books, scientific journals and so on. The results and discussion that in Islamic law, illegitimate children have limited inheritance rights, namely only the right to inherit from the mother and her family, without inheritance rights from the father. This is based on the view that illegitimate children do not have a legal bond with their father, but it is important to align the principles of Islamic law and positive law in regulating the inheritance rights of illegitimate children in order to realize justice and legal certainty for all parties. This harmonization effort will not only protect illegitimate children, but also strengthen the national inheritance law system as a whole